HOW POLICY SHAPES INVESTMENT OPPORTUNITIES? COMPARATIVE INSIGHTS FROM ASIA AND AFRICA - Abu Bakarr S Turay; Ali Maksum; Dauda Alusine Kuyateh (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
During President Trump's first term, he declared a US-China trade war, which formed numerous opportunities for developing countries. It also urges multinational corporations to relocate their manufacturing factories outside of the US-China region to prevent further increasing tariff. This study used